Scope of Tourism to the Growth of Kerala Economy - Haseena. V.A (POST GRADUATE DEPARTMENT OF COMMERCE AND MANAGEMENT STUDIES SRI C ACHUTHA MENON GOVERNMENT COLLEGE, THRISSUR, KERALA, 2013)
Tourism is one of the fast growing industries in the world. When considering India, undoubtedly there is an unlimited scope of tourism development in the South Indian state of Kerala which would definitely bring up the economic growth of the country. Kerala is today the most acclaimed tourist destination in India with its Super brand 'God's Own Country' and is continuing as one of the prime tourist destinations of South Asia. Tourism industry in Kerala not only facilitates infrastructure development but also help in balanced and sustainable regional growth by generating income and creating employment opportunities. There is a high degree of widening the service in this industry with the help of technology and infrastructure in connection with the globalisation process. the scope and opportunity of developing the tourism in Kerala, focusing and exploring its natural resources and cultural inheritance and the very traditional nature of simplicity and service is very essential to examine in the present context of development scenario